SASTRA ANAK DAN PEMBENTUKAN KARAKTER - Nurgiyantoro, Burhan (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Childrens Literature and Character Building. This article aims todescribe roles and strategies of the learning of childrens literature in charactereducation. In terms of the materials, literature has already contained rawmaterials to build childrens character. Literature is culture in action containinglife models. The concept of people with ideal character highly appreciatingmorality and great values is concretely manifested in the story characters attitudesand behaviors. Children can imitate the heroes with ideal norms and take theirattitudes and behaviors as examples. Moreover, at their age, children like to imitatebehaviors of people that they admire. To prevent literature learning from becomingrote learning, teachers and parents should work in synergy to help children read,understand, and give examples of concrete attitudes and behaviors so that theinternalization process takes place. Therefore, story-telling activities for childrenshould be routinely conducted and reading habits should be inculcated since theearly age.Keywords: childrens literature, character building, culture in behaviors